Effective Cibenzoline Treatment in a Patient With Midventricular Obstruction After Transcatheter Aortic Valve Implantation. (January 2016) - Isobe, Sarasa; Ieda, Masaki; Kohno, Takashi; Nishiyama, Takahiko; Maekawa, Yuichiro; Tsuruta, Hikaru; Murata, Mitsushige; Yashima, Fumiaki; Yanagisawa, Ryo; Tanaka, Makoto; Inami, Shu; Nasuno, Takahisa; et al.
Abstract : Supplemental Digital Content is available in the text.